Unusual presentation of intestinal myiasis due to Musca domestica: A report of two cases - Achra, Arvind; Prakash, Pradyot; Verma, Bhupendra; Amar, Askash (Asian Journal of Medical Sciences, 2014)
Intestinal myiasis is an accidental phenomenon that occurs when fly eggs or larvae are ingested in food and passed into the faeces as larvae. It is usually transient and the patients are asymptomatic. In some cases, however, the passage of larvae may be associated with symptoms. The present case reports describe two such cases, one associated with persistent passage of maggots in stool and urticaria; and other associated with altered bowel habits and inflammatory changes in lower gastrointestinal tract. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10803 Asian Journal of Medical Sciences Vol.6(1) 2015 124-126